Sequential and Selective Extraction of Copper in Different Soil Phases and Plant Parts from Former Industrialized Area - Kaplan, Olcay; Kaya, Gokce; Yaman, Mehmet (Taylor & Francis Inc, 2011)
Copper (Cu) is an essential trace element for all living organisms; however, excess amounts in soil, plants, and food have negative impacts on the environment and human health. The aim of this study was to determine Cu levels in different chemical phases of soils and the relationship between Cu levels in soil phases and concentrations in plants. Soils and plants grown in these soils from an industrialized area in Turkey were analyzed using a selective and four-stage sequential extraction procedure. Copper levels in exchangeable fractions were found up to 658 mg kg(-1) while total levels were in the range of 133-5609 mg kg(-1). Copper concentrations in plant parts (roots and stem) were in the range of 2.6-240 mg kg(-1). The exchangeable forms of Cu were in the range of 3-22% of total Cu concentrations. The relationships were observed between soil Cu and Rumex plant Cu, and soil Cu and root of Brassicasea plant Cu.
Keywords: Copper; extraction; plant; soil; speciation